PEMEROLEHAN BAHASA KEDUA PADA ANAK BERKEBANGSAAN SOMALIA DI TANGERANG SELATAN - Dedy Eko Aryanto (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
Ahmad, a four-year 8-month-old Somali child who lives in South Tangerang, communicates in an English speaking family, occasionally his mother communicates using Indonesian. Ahmad is unique in speaking both languages. He can speak English fluently and speak Indonesian mixed with English fluently too. The purpose of this study is to determine the second language acquisition system and forms of second language understanding for Ahmad, both in the structure of question sentences and answer sentences. The research data is in the form of language. There are words and sentences that Ahmad used when having a dialogue with the researcher and his mother. Information is collected using